2000
DOI: 10.2143/ac.55.4.2005747
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the fibrinolytic system components during acute myocardial infarction

Abstract: The purpose of this study was to evaluate the changes in tissue-plasminogen activator (t-PA), plasminogen activator inhibitor - type 1 (PAI-1) and D-dimer (DD) antigen plasma levels in acute myocardial infarction (AMI) patients after thrombolytic therapy with two different thrombolytic agents, rt-PA or acetyl-streptokinase and to find out any correlation between the plasma t-PA, PAI-1 and DD levels with the infarct size as it is estimated from the peak of serum CPK levels. The plasma antigen levels of t-PA, PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The authors have explained these results by the time lag of 6 hours in the hepatic synthesis of CRP, 4) by the association of CRP elevation with preinfarction unstable angina pectoris accompanied by silent myocardial ischemia, which acts as ischemic preconditioning, and by the inductive effect of inflammation on expression of angiogenic growth factors associated with reduced infarct size and on endogenous production of nitrous oxide, which protects myocardium from reperfusion injury. 40) On the other hand, also consistent with our results, both basal levels of PAI-1 in the population-based studies 41,42) and its acute-phase levels including those assessed on admission in the clinical studies [10][11][12][13] have been shown to be elevated in AMI patients. However, the mechanisms behind this association is unclear.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The authors have explained these results by the time lag of 6 hours in the hepatic synthesis of CRP, 4) by the association of CRP elevation with preinfarction unstable angina pectoris accompanied by silent myocardial ischemia, which acts as ischemic preconditioning, and by the inductive effect of inflammation on expression of angiogenic growth factors associated with reduced infarct size and on endogenous production of nitrous oxide, which protects myocardium from reperfusion injury. 40) On the other hand, also consistent with our results, both basal levels of PAI-1 in the population-based studies 41,42) and its acute-phase levels including those assessed on admission in the clinical studies [10][11][12][13] have been shown to be elevated in AMI patients. However, the mechanisms behind this association is unclear.…”
Section: Discussionsupporting
confidence: 90%
“…16) Concerning this last issue, among the factors associated with the occurrence of LVD after AMI, the presence of diabetes 45,46) and larger enzymatic infarct size 31,32) have also been shown to be associated with increased levels of PAI-1 in this setting. 10,13) Therefore, it is not possible to conclude that our finding of an association between higher PAI-1 levels and the occurrence of CS in AMI patients is merely due to a pre-existing medical condition or severity of the ongoing disease process. However, in a number of experimental studies, PAI-1 has been proposed to play an important role in ventricular remodelling after AMI.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…High levels of PAI-1 inhibit the fibrinolytic system and promote thrombosis and uncontrolled fibrin deposition (38,39). The level of PAI-1 strongly correlates with the size of myocardial infarction (40) and unfavorable outcomes in severe multiple organ failure in sepsis, disseminated intravascular coagulation (41)(42)(43)(44), and pleural injury (26). It has been unclear as to whether there is a molecular mechanism that connects physiological effects of high levels of EC DNA and PAI-1 to the fibrinolytic system.…”
mentioning
confidence: 99%
“…High levels of PAI-1 inhibit the fibrinolytic system by preventing the formation of plasmin from plasminogen and promote thrombosis (6, 7). An elevated concentration of PAI-1 correlates with an increased rate of ischemic arterial disease (8) as follows: atherosclerosis, angina pectoris (9 -14), and myocardial infarction (15)(16)(17)(18)(19)(20)(21)(22), as well as with deep vein thrombosis and disseminated intravascular coagulation (23-25). Because complete inactivation of PAI-1 is not lifethreatening (26 -28), the development of new approaches to the therapeutic neutralization of PAI-1 is a subject of many studies (for review see Refs.…”
mentioning
confidence: 99%